Partial least squares modelling of classroom layouts to learning motivation and student performance - Ong, Karl Benedict N. (Animo Repository, 2019)
Educational ergonomics is the branch of ergonomics that attempts to understand the interaction between educational design and student performance. Aside from the curriculum and teaching quality, the design of the schools and classrooms affect a student’s learning motivation and ability. A study by Smith (2011) identified significant factors in classroom ergonomics, and an extension proposed by Cheryan et al. (2014) is the consideration of classroom layout as a design factor. The inequality of access to resources causes inequality to the development of students. While building constructions and renovations require large amount of investments, classroom layout was discovered to be a low-cost design factor that can significantly improve the performances of students in class. There are three components of classroom layouts, namely seat arrangement, seat distances, and seat assignment schemes, found in literature. However, there is no study that simultaneously consider these factors with its effect to learning motivation and student performance. Most studies in educational ergonomics use objective test scores to measure performance, but performance can also be measured by participation. This study examined the students’ performance in both measures. Aside from this, other factors considered to affect the relationships in the model are class subjects and a student’s seat location in the classroom. Before assessing the relationship, the proper measurement tools were developed and validated. The research included the formulation of a survey questionnaire, participation assessment tool, and examinations to accurately measure each construct. Through these tools and a participatory ergonomic research approach, the researcher successfully explored the relationships of classroom layouts to learning motivation and student performance of Alternative Learning System students. Subjects of the study included 30 students who are aged between 18 to 25 who participate in the ALS program of De La Salle University. Alternative design combinations were generated from a partial factorial design of experiments, and there was a total of 26 runs conducted with the same set of ALS students. Results were analyzed through the partial least squares modelling in SMART PLS. It was found that all path coefficients in the model are supported, therefore these are significant. However, their ability to predict the endogenous variables are unequal. It was found that social interaction is a strong predictor and participation level is a stronger indicator of student performance. It was found that the significance of motivation and participation level of students are greatest for the u-shaped layout. Seat distances influences the relationships for boxed and u-shaped, but not for clustered design. Moreover, it was found that is no significant change in the relationships if teachers or students dictate their seat assignment, but varying class subjects and seat location significantly affects the relationships of the constructs. The validated relationships between classroom layouts could lead to the standardization of classroom and building designs that are aimed to optimize resources and performance of students. Finally, this study opens the opportunity to test the theory in other applications of room layouts and examine whether there are relationships between design and performance.